Evaluation of the effectiveness of behavioural economic incentive programmes for the promotion of a healthy diet and physical activity: a protocol for a systematic review and network meta-analysis - Gareth Mckay; Ammarin Thakkinstian; John Attia; Oraluck Pattanaprateep; Boonsong Ongphiphadhanakul; Suparee Boonmanunt (BMJ Open)
Introduction Obesity and being overweight are major risk factors for metabolic syndrome and non-communicable diseases. Despite the recommendation that a healthy diet and physical activity can reduce the severity of these diseases, many fail to adhere to these measures. From a behavioural economic perspective, adherence to such measures can be encouraged through financial incentives. However, additional related behavioural economic approaches may improve the effectiveness of an incentive programme. As such, we have developed a protocol for a systematic review and network meta-analysis to summarise the current evidence from financial incentive programmes with and without behavioural economic insights for promoting healthy diet and physical activity.Methods and analysis Previous systematic reviews, meta-analyses and individual studies were identified from Medline and Scopus in June 2020 and will be updated until December 2020. Individual studies will be selected and data extracted by two reviewers. Disagreement will be resolved by consensus or adjudicated by a third reviewer. A descriptive analysis will summarise the effectiveness of behavioural economic incentive programmes for promoting healthy diet and physical activity. Moreover, individual studies will be pooled using network meta-analyses where possible. I2 statistics and Cochran’s Q test will be used to assess heterogeneity. Risk of bias and publication bias, if appropriate, will be evaluated, as well as the overall strength of the evidence.Ethics and dissemination Ethics approval for a systematic review and meta-analysis is not required. The findings will be published in a peer-reviewed journal.PROSPERO registration number CRD42020198024.